2019
DOI: 10.1021/acs.jpcb.9b00965
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Deprotonated Pyrrole Nitrogen of the Bilin-Based Photoreceptor by Raman Spectroscopy with an Advanced Computational Analysis

Abstract: Phytochrome and cyanobacteriochrome utilize a linear methine-bridged tetrapyrrole (bilin) to control numerous biological processes. They show a reversible photoconversion between two spectrally distinct states. This photocycle is initiated by a CC double-bond photoisomerization of the bilin followed by its thermal relaxations with transient and/or stationary changes in the protonation state of the pyrrole moiety. However, it has never been identified which of the four pyrrole nitrogen atoms is deprotonated. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 37 publications
10
37
1
Order By: Relevance
“…The similarity in the down-filed shift of 15 (Figs. 3 and S8), which is consistent with our previous resonance Raman spectroscopy and QM/MM simulation experiment in RcaE (53). Deprotonation in the NB nitrogen is also consistent with solid-state NMR of in vitro-prepared AnPixJ proteins harboring deprotonated PCB fraction for its Pg photoproduct state (54).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The similarity in the down-filed shift of 15 (Figs. 3 and S8), which is consistent with our previous resonance Raman spectroscopy and QM/MM simulation experiment in RcaE (53). Deprotonation in the NB nitrogen is also consistent with solid-state NMR of in vitro-prepared AnPixJ proteins harboring deprotonated PCB fraction for its Pg photoproduct state (54).…”
Section: Discussionsupporting
confidence: 90%
“…The C15-Z,anti structure for the Pg state of RcaE (Fig. 4, left panel) is supported by recent our resonance Raman spectroscopy of RcaE (53). That study showed that the observed resonance Raman spectra in the Pg state of RcaE were well reproduced by the simulated spectra of C15-simulation (53).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In contrast, green/red CBCRs have a reversed photocycle: the greenabsorbing 15Z dark state photoconverts to yield a red-absorbing 15E photoproduct. This subfamily uses a protochromic mechanism, whereby photoconversion triggers a proton transfer to the chromophore and induces a spectral red shift (2,38).…”
Section: /Bodymentioning
confidence: 99%